2019
DOI: 10.1002/cam4.2771
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of CpG 5962 in L1 of the human papillomavirus 16 genome as a potential predictive marker for viral persistence: A prospective large cohort study using cervical swab samples

Abstract: Several studies have demonstrated that the viral genome can be methylated by the host cell during progression from persistent infection to cervical cancer. The aim of this study was to investigate whether methylation at a specific site could predict the development of viral persistence and whether viral load shows a correlation with specific methylation patterns. HPV16-positive samples from women aged 20-29 years (n = 99) with a follow-up time of 13 years, were included from a Danish cohort comprising 11 088 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…With regard to specific CpG sites of HPV 16 with good predictive utility in our study, CpG 5602 in L1 gene had won the top AUC value in the detection of CIN3/AIS in Clarke et al's nested case-control study reaching 0.84 [18]; CpG 6650 and 7034 in L1 gene in two studies of Chinese population also showed strong 16 positive women in our current study [31]. Albeit with the consensus on the role of LCR region in regulating viral gene expression [29,30], it remains undetermined which methylation patterns, hypomethylation or hypermethylation, in this region are associated with the risk of cervical cancer [25,27,31,32]. Our current study showed that high methylations in CpG 31, 37, or 43 were associated with CIN3+ risk, which were consistent with Sun's finding [27], but different from Fertey's finding s [32].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…With regard to specific CpG sites of HPV 16 with good predictive utility in our study, CpG 5602 in L1 gene had won the top AUC value in the detection of CIN3/AIS in Clarke et al's nested case-control study reaching 0.84 [18]; CpG 6650 and 7034 in L1 gene in two studies of Chinese population also showed strong 16 positive women in our current study [31]. Albeit with the consensus on the role of LCR region in regulating viral gene expression [29,30], it remains undetermined which methylation patterns, hypomethylation or hypermethylation, in this region are associated with the risk of cervical cancer [25,27,31,32]. Our current study showed that high methylations in CpG 31, 37, or 43 were associated with CIN3+ risk, which were consistent with Sun's finding [27], but different from Fertey's finding s [32].…”
Section: Discussionsupporting
confidence: 53%
“…Albeit with the consensus on the role of LCR region in regulating viral gene expression [29,30], it remains undetermined which methylation patterns, hypomethylation or hypermethylation, in this region are associated with the risk of cervical cancer [25,27,31,32]. Our current study showed that high methylations in CpG 31, 37, or 43 were associated with CIN3+ risk, which were consistent with Sun's finding [27], but different from Fertey's finding s [32]. These discrepancies among these observations may partly result from study design (e.g., prospective cohort, nested case-control, or cross-sectional study), methylation assays (e.g., pyrosequencing or next-generation bisulfite sequencing), study population, and/or disease endpoints (e.g., CIN2+ versus CIN3 in our study).…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that the methylation status of the viral genome at position 5,962, corresponding to the L1 gene was significantly higher in samples of the virus isolated from women with persistent infection compared with those isolated from women with transient infection. This suggests that hypermethylation of the L1 gene of HPV16 is associated with viral persistence ( 62 ). A similar result has also been reported in another study, in which a high level of methylation was found in several CpG islands of the L1 gene of HPV16 and this condition was shown to be associated with an increased risk of persistent infection by HPV16( 63 ).…”
Section: Epigeneticsmentioning
confidence: 99%
“…Upon HPV infection, the viral and host DNA methylation facilitates viral persistence and carcinogenesis. The grade of HPV L1 methylation is indicative of disease severity and persistent HPV infection in the cervix [27], while persistent HPV infection is due the hypermethylation of the E2 binding site on the Long Control region (LCR) [28].…”
Section: Introductionmentioning
confidence: 99%